AB1040 Comparison of Adherence and Dosing Interval of Subcutaneous anti-TNF Biologics in Inflammatory Arthritis from A Canadian Administrative Database. (15th July 2016) - Bhoi, P.; Bessette, L.; Bell, M.; Tkaczyk, C.; Nantel, F.; Maslova, K.
Abstract : Objectives: Subcutaneous (SC) anti-TNF agents such as Golimumab (GLM) Adalimumab (ADA), Etanercept (ETA) and Certolizumab pegol (CZP) have been used for many years for the treatment of inflammatory arthritis. It is known that across diseases, and especially with chronic diseases, adherence to therapy is an important modifiable factor that may compromise treatment outcomes. The aim of this analysis was to compare adherence and dosing interval of SC anti-TNF in the treatment of inflammatory arthritis. Methods: We used the IMS Brogan database which combined both private (PDP) and public drug plan databases of the provinces of Ontario (OPDP) and Quebec (RAMQ). Target drugs included SC anti-TNF biologics for indication of rheumatoid arthritis, ankylosing spondylitis, and psoriatic arthritis combined. The Index period was from January 1, 2010 - June 30, 2012 and patients were followed for 24 months through June 30, 2014. Patient selection criteria were adult patients newly prescribed a target biologic drug with at least three prescriptions and retained on therapy at 24 months. Recommended dose regimens as per the Canadian product monographs were used to compare actual vs. expected drug utilization. The compliance rate (MPR) was calculated as the estimated days' supply in the defined period divided by the number of days in the defined period. Patients who scored >80% were considered adherent. For dose-interval analysis, the average days between units was estimated by taking the total days on therapy and dividing by the number of units the patient received. A unit is a syringe or vial; the total amount of drugs dispensed (in mg) were standardized at units as per the following: GLM: 50 mg; ADA: 40 mg; ETA: 50 mg; CZP: 200 mg. P-value obtained from Chi-square and Pair-wise comparison tests for statistical differences on the proportion of adherent patients; p-value <0.05 is considered to be statistically significantly different. Results: There were 4, 035 new patients on target biologic drugs with at least three prescriptions and retained on therapy at 24 months. The number of patients for each biologic drug used was 683, 1400, 1765 and 187 for GLM, ADA, ETA and CZP, respectively. The data source was as follow: PDP national (N=2509), RAMQ (N=634) and OPDP (N=892). In 24 months-retained patients, there was a greater proportion of GLM-treated adherent patients (n=595/683, 87%, p<0.0001) compared to ADA- (n=1044/1400, 75%), ETA- (n=1285/1765, 73%) or CZP-treated patients (132/187, 71%). We also investigated the number of patients receiving biologic drug at a shorter dosing interval. That proportion was similar between groups and was 5%, 6%, 12% and 4% in GLM- (≤26 days), ADA- (≤12 days), ETA- (≤6 days) and CZP-treated patients (≤12 days), respectively. Conclusions: In this real life Canadian administrative database, GLM has better adherence compared to other SC biologics. The reason for this difference and impact on long-term outcomes are currently under investigation. Disclosure of Interest: P. Bhoi Employee of: Janssen Inc., L. Bessette: None declared, M. Bell: None declared, C. Tkaczyk Employee of: Janssen Inc., F. Nantel Employee of: Janssen Inc., K. Maslova Employee of: Janssen Inc.